Program Makan Bergizi Gratis (Mbg) Sebagai Utopia/Distopia (Studi Hermeneutika Kekuasaan) - Roos, David. O. (HIPOTESA - Jurnal Ilmu-Ilmu Sosial, 2025)
The MBG program has significant potential to improve children's health, the agricultural sector, and the local economy, as well as increase student academic achievement and school attendance. However, program implementation faces various challenges, including budget sustainability, regulations, stakeholder synergy, the risk of diversion of funds, and compliance with nutrition and food safety standards. Strengthening regulations and stable funding are crucial to ensure the sustainability of the MBG program.